Alakazam! : tricks for veteran magicians - Barnhart, Norm (Amazing magic tricks., 2018)
"Describes how to prepare and perform several magic tricks for master level magicians. Includes embedded links for added online instructional videos that can be accessed with the Capstone 4D app"--